Intermedial specificity of the collection of Paul Eluard and Man Ray "Free Hands" - Івлєва, Юлія Олегівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
This article is part of a more thorough study of the phenomenon of "picto-poetry" on the materials of the collection of Paul Eluard and Man Ray "Les Mains libres". Surrealism as an avant-garde trend does not accidentally attract the attention of modern Ukrainian and foreign scholars, because it is precisely this personification of the crisis of society and art in general, which is characteristic of transitional eras. The science has well researched the history of this trend, its philosophy, the specifics of creativity. The "white spot" remains what could be called the "morphology" of surreal poetry, that is, the system of its genres. This article is a contribution to the development of a system of surrealistic genres, in particular, a contribution to the development of the phenomenon of "picto-poetry", which has hardly been studied in modern literary criticism. As it is known, it was precisely in such revolutionary times, when society was undergoing a revolution in all spheres of life, that there is a tendency to mix not only different genres, but also types of art. Intermediality is a practical embodiment of the synthesis of arts in one work and is considered as a one of the integral features of the aesthetics of the avant-garde, and especially – of surrealism. This study shows how the main features of intermediality are expressed in the visual poetry of the surrealists, Paul Eluard in particular, on the example of the collection "Free Hands". In addition, an analysis of one of the collection’s duopoem proves that his poetry is rich in a kind of associativity, imagery at the linguistic level, the interpenetration of borders, its poetics is supplemented by the use of graphic art tools, elements of curly verse as part of “picto-poetry”. The creative exploitation of the resources of the unconscious as the main artistic method allows authors to ignore the boundaries between different types of art. Working in various fields, artists organically continue and deepen each other’s works: there is a kind of intrusion of one artistic speech into another.